2010
DOI: 10.1038/pj.2010.121
|View full text |Cite
|
Sign up to set email alerts
|

Cloud points in aqueous solutions of poly(N-isopropylacrylamide) synthesized by aqueous redox polymerization

Abstract: The mean-square radius of gyration, second virial coefficient and intrinsic viscosity were determined in methanol at 25.0 1C for poly(N-isopropylacrylamide) (PNIPA) samples in the range of weight-average molecular weight M w from 1.04Â10 5 to 2.65Â10 6 , which were synthesized by aqueous redox polymerization using a redox catalyst consisting of ammonium persulfate and sodium metabisulfite. Analyses of the quantities showed that the samples have almost the same degree of branching as that of PNIPA samples previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…However, the value of the cloud‐point could be influenced by neighboring hydrophilic/hydrophobic groups. [ 11,14 ] Generally, hydrophobic groups lower the cloud‐point while hydrophilic groups shift the cloud‐point toward higher temperature. [ 15 ] In Figure 3, one can observe that, whatever the value of X TEMPO + , the swelling factors values are slightly decreasing as temperature increases and dramatically drop down between 70 and 80 °C.…”
Section: Resultsmentioning
confidence: 99%
“…However, the value of the cloud‐point could be influenced by neighboring hydrophilic/hydrophobic groups. [ 11,14 ] Generally, hydrophobic groups lower the cloud‐point while hydrophilic groups shift the cloud‐point toward higher temperature. [ 15 ] In Figure 3, one can observe that, whatever the value of X TEMPO + , the swelling factors values are slightly decreasing as temperature increases and dramatically drop down between 70 and 80 °C.…”
Section: Resultsmentioning
confidence: 99%
“…The PNIPA sample R5 was prepared by aqueous redox polymerization using a redox catalyst consisting of ammonium persulfate, (NH 4 ) 2 S 2 O 8 (Nacalai Tesque, Inc., Kyoto, Japan), as the oxidant and sodium metabisulfite, Na 2 S 2 O 5 (Nacalai Tesque Inc.), as the reductant, according to the procedure reported by Wooten et al 17 The procedure used for the polymerization and purification of the sample was the same as that described in our previous paper, 5 except the present sample was not fractionated. We note that almost all of the initiating chain ends of the sample R5 are considered to be anionic sulfonate groups.…”
Section: Experimental Procedures Materialsmentioning
confidence: 99%
“…Recently, we performed a series of experimental studies on the phase behavior of aqueous poly(N-isopropylacrylamide) (PNIPA) solutions, [1][2][3][4][5] which exhibited lower critical solution temperature miscibility near human body temperature that was caused by the breakdown of hydrogen bonds between polymers and the surrounding water molecules. During the course of these studies, [1][2][3][4][5] we observed that the phase behavior was not as simple as it is generally considered to be and that cloud-point curves were affected considerably by the nature of the PNIPA chain-end groups, as well as by the degree of branching.…”
Section: Introductionmentioning
confidence: 99%
“…Equation is often used for describing the free‐radical generation by the persulfate/metabisulfite redox pair . However, a variety of reports in the literature have proposed the bisulfate anions as reductant in the redox reaction, which is in equilibrium with metabisulfite anion in aqueous medium, as described by Equation . The end‐group studies also support the idea that the reducing part of the redox pair is the bisulfite anion, Equation , rather than the metabisulfite anion in Equation .…”
Section: Introductionmentioning
confidence: 99%
“…However, a variety of reports in the literature have proposed the bisulfate anions as reductant in the redox reaction, which is in equilibrium with metabisulfite anion in aqueous medium, as described by Equation . The end‐group studies also support the idea that the reducing part of the redox pair is the bisulfite anion, Equation , rather than the metabisulfite anion in Equation . normalS2normalOnormal82+normalS2normalOnormal52krSOnormal4+SOnormal42+normalS2normalOnormal5 normalS2normalOnormal52+normalH2O2HSO3 normalS2normalOnormal82+HSOnormal3krHSOnormal3+SOnormal4+SOnormal42 HSOnormal3+SOnormal4SOnormal42+HSOnormal3 Reactions and are expected to dominate under bisulfite in excess over persulfate and with a polymerization temperature of around 40 °C, thus producing polymers with mainly sulfonate end‐groups.…”
Section: Introductionmentioning
confidence: 99%